Conveyor Speed Control with Fuzzy-PID - Minh-Nam Phan; Van-Thao Nguyen; The-An Nguyen; Thi-Ngoc-Thao Nguyen; Thanh-Binh Nguyen; Thi-Hong-Lam Le; Van-Hiep Nguyen; Hoang-Lam Le; Van-Phuc Nguyen; Phong-Nam Huynh; Vi-Cuong Hong; Tuan-Minh Truong; Kieu-Vinh Nguyen; Huu-Nhan Tran (Journal of Fuzzy Systems and Control, 2026)
Conveyor belt systems are essential components in industrial automation, but controlling their speed accurately is a significant challenge. Classic PID controllers, while common, struggle to handle the inherent nonlinearities of these systems, such as varying friction and sudden load changes. The adaptive Fuzzy-PID controller, which auto-tunes its parameters, has been proposed as a superior alternative. However, most existing research is limited to software simulations, leaving a gap between theoretical performance and practical, real-world applicability. This paper addresses this gap by presenting the complete design, construction, and experimental verification of a Fuzzy-PID controller implemented on a physical conveyor belt model. The methodology includes system identification via multi-sine input to extract a baseline transfer function, followed by the deployment of the control algorithm on an embedded Arduino Nano microcontroller. Experimental results are presented and directly compared with those of a conventional PID controller to evaluate its performance. Quantitative findings confirm that the embedded Fuzzy-PID controller provides superior performance, reducing the rise time to 0.16 s (from 0.20 s) and significantly decreasing the settling time to 0.56 s (a 48.1% improvement over the PID's 1.08 s). Furthermore, the steady-state error was reduced by 36.4%, demonstrating its superior stability and efficiency in a practical hardware environment and confirming its feasibility for industrial applications.